2012
DOI: 10.1063/1.4767224
|View full text |Cite
|
Sign up to set email alerts
|

Negative Poisson's ratio and piezoelectric anisotropy of tetragonal ferroelectric single crystals

Abstract: Orientational dependences of the Poisson's ratio have been calculated for several perovskite tetragonal ferroelectric singe crystals: 0.67Pb(Mg1/3Nb2/3)O3–0.33PbTiO3, PbTiO3, and BaTiO3. All these crystals are shown to have negative values of Poisson's ratio in some crystallographic directions thus being so-called partial auxetics. The largest negative Poisson's ratio values possess 0.67Pb(Mg1/3Nb2/3)O3–0.33PbTiO3 single crystals. The thermodynamic restrictions for the d33 and d31 piezoelectric moduli of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Although it has been shown theoretically that the Poisson's ratio for isotropic materials is limited to the range of −1.0 to 0.5, it was usually thought that the Poisson's ratio of materials is a positive constant due to the limited experimental observations of materials with negative Poisson's ratios. Nevertheless, it has been largely demonstrated recently that the Poisson's ratio exhibits variability with crystallographic axes, and negative Poisson's ratios arise along certain crystallographic directions in materials with large anisotropy . Moreover, it has been also demonstrated that the magnitude of the Poisson's ratio of materials in bulk or film forms can be tuned with external factors, such as chemical composition, temperature, electrical field, pressure, and misfit strain, usually accompanied with structural transitions and changes of other physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been shown theoretically that the Poisson's ratio for isotropic materials is limited to the range of −1.0 to 0.5, it was usually thought that the Poisson's ratio of materials is a positive constant due to the limited experimental observations of materials with negative Poisson's ratios. Nevertheless, it has been largely demonstrated recently that the Poisson's ratio exhibits variability with crystallographic axes, and negative Poisson's ratios arise along certain crystallographic directions in materials with large anisotropy . Moreover, it has been also demonstrated that the magnitude of the Poisson's ratio of materials in bulk or film forms can be tuned with external factors, such as chemical composition, temperature, electrical field, pressure, and misfit strain, usually accompanied with structural transitions and changes of other physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric materials may have different crystal symmetries, the electromechanical properties of piezoelectric materials can be regarded as the comprehensive response to anisotropic characteristics. Poisson’s ratio can characterize the anisotropy of materials, 21 and some researches have revealed that the Poisson’s ratio is associated with the piezoelectric strain coefficients and electromechanical coupling coefficients in the transversely isotropic piezoelectric ceramics 22–24 . Kahn 25 proved that anisotropic porosity can reduce d31/d33 in PZT by changing the Poisson’s ratio.…”
Section: Introductionmentioning
confidence: 99%
“…This counter-intuitive property can be utilized to strengthen mechanical properties for the purpose of improving the crack resistance [1], increasing the fracture toughness [2,3], or providing higher sound absorption capacity [4]. Since Lakes first developed NPR foam structures in 1987 [5], the research work on NPR metamaterials modeling, design and manufacturing as well as their potential applications has advanced considerably [6][7][8][9][10][11][12][13][14]. In 1985, Kolpakov proposed a method for approximating the average elastic characteristics of framework structures of periodic configuration, and constructed fine-celled framework structures with negative Poisson's ratios [15].…”
Section: Introductionmentioning
confidence: 99%